2014
DOI: 10.1371/journal.pone.0097273
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Folic Acid Supplementation on Adverse Maternal and Fetal Outcomes

Abstract: Although there is accumulating evidence regarding the additional protective effect of folic acid against adverse pregnancy outcomes other than neural tube defects, these effects have not been elucidated in detail. We evaluated whether folic acid supplementation is associated with favorable maternal and fetal outcomes. This was a secondary analysis of 215 pregnant women who were enrolled in our prior study. With additional data from telephone interviews regarding prenatal folic acid supplementation, existing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 27 publications
2
40
0
2
Order By: Relevance
“…Random effects meta‐analysis of eight observational studies showed significantly lower odds of preeclampsia overall with folic acid supplementation in comparison to no supplementation: OR = 0.78 (95% CI 0.63, 0.98); I‐squared = 67% (moderately high heterogeneity). Figure shows a Forest Plot of the meta‐analysis of maternal folic acid supplementation on the outcome of preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random effects meta‐analysis of eight observational studies showed significantly lower odds of preeclampsia overall with folic acid supplementation in comparison to no supplementation: OR = 0.78 (95% CI 0.63, 0.98); I‐squared = 67% (moderately high heterogeneity). Figure shows a Forest Plot of the meta‐analysis of maternal folic acid supplementation on the outcome of preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…No non‐English language studies were found for full text review. Ten studies were assessed as meeting the a priori inclusion criteria and were included in this systematic review …”
Section: Resultsmentioning
confidence: 99%
“…The folate level is shown to be a risk factor for NTDs. 16,17 Studies have shown that the proper intake of folic acid during peri-gestational period can decrease the chances of having NTDs in newborns. It has also been observed that administration of 5-MTHF is more effective than simple folic acid intake at improving folate status 23 , thus providing a protective effect in preventing neural tube defects in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of developed countries, folic acid supplementation (at least 400 µg) is recommended for 2–3 months prior to conception and throughout pregnancy into the postpartum period 6. This been adopted as a worldwide strategy to reduce the incidence of fetal neural tube defects (NTD) such as anencephaly, spina bifida and meningomyelocele.…”
Section: Discussionmentioning
confidence: 99%